Osoba z głęboką wieloraką niepełnosprawnością jako uczestnik interakcji - Jerzyk, Monika (Studia Edukacyjne, 2024)
The article attempts to describe the communication competences of people with profound intellectual and multiple disabilities. It presents a person with profound intellectual and multiple disabilities in the context of his or her biographical experiences, including interactions and relationships. It shows communication as a process based on reciprocity, thus emphasizing the importance of actions taken by both parties of this interaction. This text contains a description of the complexity of communication methods available to people with profound intellectual and multiple disabilities and a proposal of qualitatively significant ways of acting on the part of interaction partners.